Nearly 2-Absorbing Submodules And Related Concepts - Reem T. Abdulqader; Shwkea M. Rajab (Tikrit Journal of Pure Science)
Throughout this note R is commutative ring with identity, and X be a left unitary R-module. A proper submodule K of an R-module X is called nearly prime, if whenever implies that either ( ) or [ ( ) ]. This concept us to introduce the concept of nearly prime submodule, where a proper submodule K of an R-module X is called nearly 2-absorbing submodule, if wherever , and then either ( ) or ( ) or [ ( ) ]. The aim of this paper is to study this concept, and gives some of its basic properties, characterization and examples. Furthermore, we study the relation of this concept with some kind of submodules".